Peran Pendidikan Islam Dalam Mewujudkan Rahmatan Lil ‘Alamin Pada Generasi Z Muslim - Hadmal, Hadmal; Suhartini, Suhartini; Wahida , Wahida; St. Nurhayati Ali (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Islamic education plays a strategic role in shaping the character of a Muslim generation with noble character, moderation, and a positive contribution to global society. The concept of rahmatan lil 'alamin (blessings for the universe) is a fundamental value in Islam that emphasizes compassion, justice, tolerance, and universal welfare. The main challenge today is how these values ​​can be effectively internalized by Generation Z Muslims, a generation that grew up in the digital era, globalization, and information disruption. This study aims to systematically examine the role of Islamic education in realizing the value of rahmatan lil 'alamin in Generation Z Muslims through a literature study approach. The method used is a literature review of various scientific sources in the form of books, national and international journals, and relevant documents that discuss Islamic education, the character of Generation Z, and the concept of rahmatan lil 'alamin. The study's findings demonstrate that Islamic education plays a crucial role in instilling the values ​​of religious moderation, tolerance, social empathy, and moral responsibility through curriculum integration, educator role models, and the use of digital media that adapts to the characteristics of Generation Z. Furthermore, contextual and inclusive Islamic education can serve as a means of preventing radicalism and moral degradation among young Muslims. The study's conclusions affirm that optimizing Islamic education based on the values ​​of rahmatan lil 'alamin (blessings for the universe) is highly relevant and urgent for developing a Generation Z Muslim population that is religious, humanistic, and globally minded.